DETERMINATION OF LOCUS OF CONTROL, SELF EFFICACY AND DISCIPLINE OF WORK WITH WORK SATISFACTION AS INTERVENING VARIABLES ON WORK MOTIVATION EMPLOYEE SERVICE OF THE ISLANDS PROVINCE HEALTH RIAU - Maimunah Maimunah; Jemmy Rumengan; Yunazar Manjang (Zona Manajemen: Program Studi Magister Sains Manajemen Universitas, 2019)
in this study, researchers used respondents' data, such as gender, age and duration of work of respondents to be able to provide information about the characteristics of respondents. Where from the questionnaire questionnaire distributed as many as 70 respondents using census techniques. This research is the result of a field study to obtain an answer data questionnaire that measures five main variables in this study, namely locus of control, self efficacy, work discipline, job satisfaction and employee motivation. This study uses path analysis (path analysis) to test the pattern of relationships that reveal the influence of variables or a set of variables on other variables, both direct influence and indirect influence. The results of the study are as follows: The effect of the X3 variable on X4 has a P-Values value of 0.038 <0.05, so it can be stated that the influence between X3 and X4 is significant. The effect of the X3 variable on Y has a P-Values value of 0,000> 0.05, so it can be stated that the effect of X3 on Y is significant. The effect of the X4 variable on Y has a P-Values value of 0.005> 0.05, so it can be stated that the effect between X4 on Y is significant. The influence of X1 on X4 has a P-Values value of 0.009 <0.05, so it can be stated that the influence between X1 to X4 is significant. The effect of X1 on Y has a P-Values value of 0.005> 0.05, so it can be stated that the influence between X1 on Y is significant. The effect of the X2 variable on X4 has a P-Values value of 0.001 <0.05, so it can be stated that the effect between X2 on X4 is significant. The effect of X2 on Y has a P-Values value of 0.009 <0.05, so it can be stated that the effect between X2 on Y is significant.